2019
DOI: 10.1037/tra0000389
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment noninitiation, dropout, and response for cognitive behavioral therapy for trauma nightmares.

Abstract: Baseline symptom severity on constructs targeted in treatment are the best indicators of response. Treatment initiation appears to be more significant than dropout. Identifying reasons for treatment noninitiation is needed to maximize engagement. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Patients for whom sleep disturbances cause distress and dysfunction may potentially be more motivated to participate in treatment focusing on sleep‐related PTSD symptoms than patients for whom sleep disturbances are experienced less prominently (Miller et al., 2019 ). Furthermore, it has been reported that other factors associated with the multifaceted concept of motivation, for instance illness beliefs, may impact psychotherapy outcome (Reich et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients for whom sleep disturbances cause distress and dysfunction may potentially be more motivated to participate in treatment focusing on sleep‐related PTSD symptoms than patients for whom sleep disturbances are experienced less prominently (Miller et al., 2019 ). Furthermore, it has been reported that other factors associated with the multifaceted concept of motivation, for instance illness beliefs, may impact psychotherapy outcome (Reich et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…attended at least one session) then ends treatment before reaching “mutual agreement that therapy has been completed” (Garfield, 1989 ). This excluded studies defining dropout as including patients who did not attend any sessions—consistent with Garfield ( 1989 ) and empirical literature (Kehle-Forbes et al, 2016 ; Kline et al, 2020 ; Miller et al, 2019 ), this review considers those patients as rejecting or failing to initiate treatment, rather than dropping out.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, this review focuses specifically on dropout once treatment has begun, as distinct from treatment non-initiation. In addition to theoretical arguments for this distinction (e.g., Garfield, 1989 ), empirical evidence suggests that factors predicting dropout in-treatment may differ from those predicting non-initiation (Kehle-Forbes et al, 2016 ; Kline et al, 2020 ; Miller et al, 2019 ). Kline et al ( 2020 ) suggest that nuance and specificity are likely to be lost if non-initiation and dropout during treatment are not considered as separate heterogeneous types of discontinuation.…”
Section: Introductionmentioning
confidence: 99%